A Global Perspective on Phosphorus Management Decision Support in Agriculture: Lessons Learned and Future Directions. Issue 5 (15th August 2019) - Drohan, Patrick J.; Bechmann, Marianne; Buda, Anthony; Djodjic, Faruk; Doody, Donnacha; Duncan, Jonathon M.; Iho, Antti; Jordan, Phil; Kleinman, Peter J.; McDowell, Richard; Mellander, Per‐Erik; Thomas, Ian A.; et al.
Abstract : The evolution of phosphorus (P) management decision support tools (DSTs) and systems (DSS), in support of food and environmental security has been most strongly affected in developed regions by national strategies (i) to optimize levels of plant available P in agricultural soils, and (ii) to mitigate P runoff to water bodies. In the United States, Western Europe, and New Zealand, combinations of regulatory and voluntary strategies, sometimes backed by economic incentives, have often been driven by reactive legislation to protect water bodies. Farmer‐specific DSSs, either based on modeling of P transfer source and transport mechanisms, or when coupled with farm‐specific information or local knowledge, have typically guided best practices, education, and implementation, yet applying DSSs in data poor catchments and/or where user adoption is poor hampers the effectiveness of these systems. Recent developments focused on integrated digital mapping of hydrologically sensitive areas and critical source areas, sometimes using real‐time data and weather forecasting, have rapidly advanced runoff modeling and education. Advances in technology related to monitoring, imaging, sensors, remote sensing, and analytical instrumentation will facilitate the development of DSSs that can predict heterogeneity over wider geographical areas. However, significant challenges remain in developing DSSs that incorporate "big data" in a format that is acceptable to users, and that adequately accounts for catchment variability, farming systems, and farmer behavior. Future efforts will undoubtedly focus on improving efficiency and conserving phosphate rock reserves in the face of future scarcity or prohibitive cost. Most importantly, the principles reviewed here are critical for sustainable agriculture. Core Ideas: Strategies protecting water bodies are often driven by reactive legislation. Phosphorus management focuses on plant available P and mitigating P runoff. Decision support is based on P transfer, best practices, education, and action. Recent scientific developments have rapidly advanced runoff modeling and education. DS challenges are "big data, " farming systems, and farmer behavior.